Transcription and beyond: the role of mammalian class I lysine deacetylases - Moser, Mirjam Andrea (Springer Berlin Heidelberg, 2013)
The Rpd3-like members of the class I lysine deacetylase family are important regulators of chromatin structure and gene expression and have pivotal functions in the control of proliferation, differentiation and development. The highly related class I deacetylases HDAC1 and HDAC2 have partially overlapping but also isoform-specific roles in diverse biological processes, whereas HDAC3 and HDAC8 have unique functions. This review describes the role of class I KDACs in the regulation of transcription as well as their non-transcriptional functions, in particular their contributions to splicing, mitosis/meiosis, replication and DNA repair. During the past years, a number of mouse loss-of-function studies provided new insights into the individual roles of class I deacetylases in cell cycle control, differentiation and tumorigenesis. Simultaneous ablation of HDAC1 and HDAC2 or single deletion of Hdac3 severely impairs cell cycle progression in all proliferating cell types indicating that these class I deacetylases are promising targets for small molecule inhibitors as anti-tumor drugs.